Хищные клещи-фитосейиды (Parasitiformes, Phytoseiidae) Лесостепи УССР. Сообщение II. Виды родов Katnpimodromus, Paraseiulus, Typhlodromus, Typhloctonus, Anthoseius, Phytoseius - Колодочка, Л.А. (Вестник зоологии, 1974)
An annotated list of 15 species of mites is presented. Typhlodromus longipilus N e s b i t t i s registered for the first time in the USSR and Typhlodromus pyri, Typhloctonus
squamiger, Phytoseius (Dubininellus) echinus, Ph. (D.) juvenis and Anthoseius (Aphanoseius) clavatus — species new for the Ukrainian fauna.